2015
DOI: 10.1016/j.mee.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Study on resist performance of chemically amplified molecular resists based on cyclic oligomers

Abstract: Novel resist materials are required for lithographic processing with ionization radiation such as extreme ultraviolet (EUV) and electron beam (EB) exposure tools. In this study, we synthesized positive-tone chemically amplified molecular resist materials with pendant adamantyl ester (AD) and cyclohexyl 2-propyl ether moieties based on cyclic oligomers such as noria, calixarene dimer, cyclodextrin, and pillar [5]arene, and we examined the lithographic performances of sensitivity, etching durability, and pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…It was found that these noria derivatives have high photoreactivity and produce clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using an EUV exposure tool [15][16][17][18][19][20][21][22][23]. Moreover, we clarified that the sensitivity of the resist materials was consistent with the structure of the cyclic oligomers such as noria, calixarene dimer, cyclodextrin, and pillar [5]arene [24].…”
Section: Introductionsupporting
confidence: 55%
“…It was found that these noria derivatives have high photoreactivity and produce clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using an EUV exposure tool [15][16][17][18][19][20][21][22][23]. Moreover, we clarified that the sensitivity of the resist materials was consistent with the structure of the cyclic oligomers such as noria, calixarene dimer, cyclodextrin, and pillar [5]arene [24].…”
Section: Introductionsupporting
confidence: 55%
“…Kudo et al investigated novel resist materials using pillar [5]arene platform. 286 A pillar [5]arene derivative with adamantyl moieties connected by ester bonds showed high lithographic performance, and is thus a promising candidate for high-resolution resist materials as well as noria, calix [n]arene dimers, and CDs.…”
Section: Electronic Materialsmentioning
confidence: 99%
“…In our previous report, EB and EUV resist patterning property of noria derivative with pendant adamantyl ester groups (noria-AD) were examined. The synthesized noria-AD offered 40 nm resolution resist pattern with LWR = 9.5 nm [14] in the case of EB exposure tool and a clear 26 nm resolution pattern with LWR = 8.3 nm by means of EUV exposure tool [7]. These results indicate that the present poly(THPE-co-BVOC) would have higher potential to offer higher resolution pattern using EUV lithography system.…”
Section: Eb Patterning Propertymentioning
confidence: 70%